2013
DOI: 10.1016/j.compag.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network approach to the estimation of stem water potential from frequency domain reflectometry soil moisture measurements and meteorological data

Abstract: ElsevierMartí Pérez, PC.; Gasque Albalate, M.; González Altozano, P. (2013). An artificial neural network approach to the estimation of stem water potential from frequency domain reflectometry soil moisture measurements and meteorological data. Computers and Electronics in Agriculture. 91:75-86. doi:10.1016Agriculture. 91:75-86. doi:10. /j.compag.2012.001. Dear Author, Please check your proof carefully and mark all corrections at the appropriate place in the proof (e.g., by using on-screen annotation in the PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
1
22
0
2
Order By: Relevance
“…It was also poor in total nitrogen (0.06%), available 121 potassium (0.42 meq K + 100g -1 ) and phosphorus (20.67 mg P kg -1 Olsen). A more detailed 122 description of the soil characteristics can be found in Martí et al (2013). The capacitance probes were properly installed within the active root system zone.…”
Section: Mpa 87mentioning
confidence: 99%
See 2 more Smart Citations
“…It was also poor in total nitrogen (0.06%), available 121 potassium (0.42 meq K + 100g -1 ) and phosphorus (20.67 mg P kg -1 Olsen). A more detailed 122 description of the soil characteristics can be found in Martí et al (2013). The capacitance probes were properly installed within the active root system zone.…”
Section: Mpa 87mentioning
confidence: 99%
“…The first three sensors, located at 10, 30, and 50 cm of depth, 228 covered practically 90% of the active root system (estimated during probe installation), while 229 the fourth was outside of this zone (70, 80, and 60 cm depth in the probes for treatments T1, 230 T2, and the control, respectively). More details about the installation of these probes can be 231 found in Martí et al (2013). 232 233…”
Section: Mpa 87mentioning
confidence: 99%
See 1 more Smart Citation
“…Acevedo-Opazo et al [6] suggested a methodology to extrapolate pre-dawn leaf water potential using linear combinations of ancillary data. Recently, Martí et al [7] used artificial neural networks to estimate stem water potential from soil moisture measurements and standard climatic records.…”
Section: Introductionmentioning
confidence: 99%
“…For solving regression tasks, the multilayer perceptron (MLP) is mainly used. Shafiee et al [14] have used MLP for prediction of some chemical honey parameters from color features, Marti et al [15] for the estimation of stem water potential, Maulidiani et al [16] for modeling the relationship between the bioactive compounds in Pegaga extract and antioxidant activity and Xi et al [17] for modeling effects of pressure, liquid/solid ratio and ethanol concentration on the total phenolic content of green tea extracts. For classification tasks, the self-organizing maps (SOM) or MLP networks are commonly used.…”
Section: Introductionmentioning
confidence: 99%